Pengaruh Gaya Kepemimpinan dan Produktivitas Kerja terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Depok - Faizatunnisa Faizatunnisa; Syahrial Addin; Yulia Mujiaty (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the influence of leadership style and work productivity on employee performance both partially and simultaneously. This study uses a quantitative approach with a saturated sampling method on the entire population of DPMPTSP employees totaling 59 respondents. Data were collected through questionnaires and analyzed using multiple linear regression and validity, reliability, T-test, F-test, and coefficient of determination tests with the help of SPSS software version 21. The results of the t-test that leadership style (X1) has a significant effect on work performance, can be seen from the calculated t value of 3.365> t table 2.003 and a significance value of 0.001 <0.05, Work productivity (X2) has a significant effect on performance obtained a calculated t value of 2.333> t table 2.003 and a significance value of 0.023 <0.05. The f test obtained a calculated f value of 30.680 > f table 3.16 and a significance value of 0.000 < 0.05, so it can be concluded simultaneously that leadership style and work productivity have a significant effect on employee performance. Leadership style contributes an influence of 47.6%, work productivity of 42.6%, and both simultaneously explain 52.3% of employee performance variables. These findings provide strategic recommendations for government agencies to improve employee performance through strengthening leadership and increasing work productivity.